Changes in microbial community composition affect bioactivities of mucus isolated from coral acropora millepora - Manh Cuong, Dao; Thu Hien, Phan Thi; Van Ngoc, Bui (Vietnam Journal of Biotechnology, 2022)
Antibiotic resistance is increasingly popular together with emerging diseases presents an urgent requirement for more and more discovery of novel marine bioactive compounds. Paired-end reads of 16S rRNA sequence of bacteria living in the coral Acropora millepora obtained by the Illumina next-generation sequencing technology to be processed by DADA2 pipeline, phyloseq and ggplot2 packages showed that bleached coral mucus had an alpha diversity to be higher than healthy coral mucus. The coral surface mucus layer (SML) of healthy coral exhibited higher growth inhibition activity to Vibrio parahaemolyticus test strain than that of bleached coral in any amount (10 – 30 µL). The cytotoxicity against the colon cancer cell line HCT 116 was also clearly observed when treated with healthy SML and was 1.5 times higher than mucus was taken from bleached coral. The composition of the microbial community was shifted when corals changed from a healthy state to a bleached one, resulting in the reduction of antibacterial activity and cytotoxicity.